Metaphor in Mark Forster's Album LIEBE S/W - Muhammad Reza (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study is a cognitive semantic analysis of the conceptual metaphor of the song lyrics in Mark Forster's album Liebe S/W. The method used is descriptive qualitative. The theories used are the conceptual metaphor theory (CMT) by Lakoff&Johnson (2003) as the main theory and image schema theory by Croft & Cruse (2004). The data sources in this study were taken from the lyrics of 14 German songs from the album Liebe S/W (2019) by Mark Forster. This study was carried out for the purpose of describing the characteristics of the metaphors, the types of conceptual metaphors and image schemes contained in the song lyrics in the album. Mark Forster's cognition as a singer-songwriter on the album can be seen with this study through a conceptual metaphor approach. Based on the results of the research, it is found as many as 52 data containing metaphorical expressions. Based on the analysis in accordance with Saeed's theory as a metaphor characteristic theory, it shows that there are 13 data with abstraction,15 data with conventionality, 9 data with systematicity, and 15 data with asymmetry. The ontological metaphors is the most dominant in the album. Data analysis using the Lakoff&Johnson theory shows that the conceptual metaphors are found as many as 32 ontological metaphors, 15 orientational metaphors, and 5 structural metaphors. The image schemes found are 20 containers, 4 multiplicities, 4 existences, 5 identites, 12 spaces and 1 scale. Some patterns were found based on theories, 1) metaphors with the characteristics of abstraction and asymmetry have ontological, orientational and structural conceptual metaphors with all types of image schemes. 2) metaphors with conventional characteristics only have ontological conceptual metaphor type with some image schemes, except multiplicity. 3) metaphors with systematic characteristics have ontological and orientation conceptual metaphors with image schemes, except identity and scale.